GROWTH KINETICS OF PASTEURELLA MULTOCIDA ISOLATED FROM NILI RAVI BUFFALO (BUBALUS BUBALIS) - H. N. Hussain; S. A. Khanum; M. Hussain (Journal of Animal and Plant Sciences, 2012)
Hemorrhagic septicemia (HS), caused by Pasteurella multocida, is one of the highly fatal diseases of Buffalo and mostly killed vaccines are used to safe the animals from this disease. Enhanced cell mass yield from Pasteurella multocida could help in better vaccine efficacy and process economics. In the present study, we characterized the growth pattern of Pasteurella multocida on various carbon sources by determining the specific growth rate (µ) and volumetric rate of cell mass formation (Qx). A field isolate of Pasteurella multocida Robert’s type-1 was grown on standard casein yeast extract media using glucose, maltose, galactose or sucrose as carbon source (0.3%). Higher cell mass yields were noted at 48, 32, 26 and 22 h post inoculation, respectively for glucose, sucrose, maltose, and galactose. For a further insight, carbon source concentration was increased from 0.3 to 1.0% and dry cell mass yields on glucose, fructose, maltose, galactose and sucrose were noted in shake flask culture. Maximum dry cell mass (gL-1) was obtained when sucrose used as carbon source followed by fructose. Specific growth rates of 0.319, 0.091, 0.183, 0.156 and 0.147 (h-1) respectively were noted on sucrose, glucose, fructose, maltose and galactose, respectively. Similarly, Qx was found to be significantly higher on sucrose compared with other sugars. Volumetric rate of cell mass formation were 0.205, 0.202, 0.093, 0.124, 0.166 gL- 1h -1 on sucrose, glucose, fructose, maltose and galactose respectively. There was an increase of 1.7% or a decrease of 38.1, 53.5 and 17.8% in Qx values on sucrose, fructose, maltose and galactose, respectively compared with that on glucose. The results indicated that carbon source type and concentration has significant effects on cell mass yield and optimized concentration and type of the carbon source could help in better vaccine production for HS disease control
Keywords: Pasteurella multocida; carbon sources; growth; kinetics; buffalo